Enhanced Optimal PMU Placements With Limited Observability Propagations - Xian-Chang Guo (IEEE Access, 2020)
When the power grid encounters unexpected contingencies, conventional optimal phasor measurement units (PMUs) placement formulations with unlimited observability propagations may increase the risk of losing the observability. In order to tackle out this difficulty, an enhanced optimal PMU placement (OPP) formulation with considering bounded observability propagation constraints is proposed in this paper by introducing the concept of observability propagation depth (OPD). The OPD can characterize the depth of observability propagations applied to observe a bus from its nearest PMU measurements. To depict OPDs under a mathematical programming (MP) framework, new observability propagation rules, which are also valid for a power grid remaining incomplete observability with limited PMUs, are investigated. Extensive simulations are conducted on several IEEE test-bed systems as well as the Polish-2383 system to demonstrate the feasibility and the effectiveness of the proposed formulation.